2002
DOI: 10.1176/appi.ajp.159.4.573
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Psychiatrist Ratings of Hypothetical Schizophrenia Research Protocols: Assessment of Harm Potential and Factors Influencing Participation Decisions

Abstract: Given hypothetical protocols with variable design elements, schizophrenia patients and psychiatrists made meaningful and discerning harm assessments and participation decisions. These findings suggest that schizophrenia patients may have strengths in the research consent process that may not be fully recognized. The impact of outside influences upon research enrollment decisions remains uncertain. While psychiatrists were often accurate in predicting patient responses, data suggest the importance of clarifying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 25 publications
5
77
0
2
Order By: Relevance
“…This discourse challenged these arguments by citing evidence that 'decision incapacity is the exception rather than the rule, even among people with psychotic conditions' (Deegan, 2014). For example, that studies of informed consent (Roberts et al, 2002), decisions around medication (Bunn, O'Connor, Tansey, Jones, & Stinson, 1997) or treatment goals (Becker & Drake, 2001), have concluded that people who experience psychosis are able to make rational choices. Authors argued that because it is clinicians themselves who make decisions about capacity there is a risk of an abuse of power, for example because a clinician may assume a lack of capacity in cases where an individual disagrees with them about their care (Deegan, 2014;Morant et al, 2015).…”
Section: People Experiencing Mental Health Challenges Are Able To Be mentioning
confidence: 99%
“…This discourse challenged these arguments by citing evidence that 'decision incapacity is the exception rather than the rule, even among people with psychotic conditions' (Deegan, 2014). For example, that studies of informed consent (Roberts et al, 2002), decisions around medication (Bunn, O'Connor, Tansey, Jones, & Stinson, 1997) or treatment goals (Becker & Drake, 2001), have concluded that people who experience psychosis are able to make rational choices. Authors argued that because it is clinicians themselves who make decisions about capacity there is a risk of an abuse of power, for example because a clinician may assume a lack of capacity in cases where an individual disagrees with them about their care (Deegan, 2014;Morant et al, 2015).…”
Section: People Experiencing Mental Health Challenges Are Able To Be mentioning
confidence: 99%
“…183 Both personal and altruistic benefits were evident, as has been found in other research. 181 Reasons for potential participation included a desire to gain information or understanding, to have a new experience or activity, or to share experiences with others, suggesting that there may be gaps in service provision in these areas. Reasons for non-participation in the future trial largely reflected a negative view of the treatment offered, or satisfaction with current treatment, consistent with a cost-benefit analysis.…”
Section: Major Themes (Frequency) Examplesmentioning
confidence: 99%
“…179 Barriers to participation include inconvenience, treatment preferences, aversion to randomisation, uncertainties regarding treatments, concerns regarding information and consent, and clinicians acting as a barrier. 180 The likelihood of participation in schizophrenia treatment trials is influenced by perceptions of risk, personal benefits and altruistic reasons, 181,182 although this has been little researched to date. Hypothetical willingness to participate in clinical trials ranges from 70% to 96%.…”
Section: Introductionmentioning
confidence: 99%
“…88,123 Risks associated with different kinds of research and procedures are seen differently by participants, clinicians, and different subject populations. 88,[123][124][125] As highlighted by the large online survey presented in this issue by Muroff and colleagues,126 psychiatric research may be stigmatized in the eyes of the general public-in particular, the notion that people with psychiatric disorders may lack capacity to consent appeared to drive the more restrictive views of respondents toward psychiatric research compared with research on medical disorders. This important finding should raise awareness among investigators and reviewers, indicating the need to be attuned to ongoing stigma toward psychiatric research.…”
Section: Diverse Scientific Designs and Proceduresmentioning
confidence: 99%
“…88,123 Moreover, patients are able to discern meaningfully among different, hypothetical research protocols of varying levels of potential harm. 123 In that study of decisions about washout and placebo control, patients' ratings of risk frequently differed from those of psychiatrists: patients rated the scenarios as more harmful. Roberts's team also found that willingness to participate was inversely associated with perceptions of research risks.…”
Section: Understanding/perceptions Of Riskmentioning
confidence: 99%